New Records of Mosquitoes (Diptera: Culicidae) from Bolívar State in South Eastern Venezuela, with 27 New Species for the State and 5 of Them New in the Country - Berti, Jesús; Guzmán, Hernán; Estrada, Yarys; Ramírez, Rodrigo (Frontiers in Public Health, 2015)
This is the first part of a series of studies related to mosquito ecological and biogeographic aspects. A total of 69 mosquito species (Diptera: Culicidae) was collected in sixteen localities sampled in the Gran Sabana Municipality, Canaima National Park, Venezuela. 27 mosquito species are recorded for the first time from Bolívar State, Venezuela. Five of them species are reported for the first time in Venezuela: Anopheles malefactor Dyar & Knab, 1907; Chagasia bonneae Root, 1927; Chagasia ablusa Harbach, 2009; Culex anduzei Cerqueira & Lane, 1944 and Uranotaenia leucoptera Theobald, 1907. Their medical importance is commented, and ecological and epidemiological aspects are discussed. A checklist of the mosquito species reported in the Gran Sabana County is given.